2018
DOI: 10.1038/s41598-018-34677-0
|View full text |Cite
|
Sign up to set email alerts
|

Scaffold-Hopping from Synthetic Drugs by Holistic Molecular Representation

Abstract: The discovery of novel ligand chemotypes allows to explore uncharted regions in chemical space, thereby potentially improving synthetic accessibility, potency, and the drug-likeness of molecules. Here, we demonstrate the scaffold-hopping ability of the new Weighted Holistic Atom Localization and Entity Shape (WHALES) molecular descriptors compared to seven state-of-the-art molecular representations on 30,000 compounds and 182 biological targets. In a prospective application, we apply WHALES to the discovery of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 49 publications
(60 reference statements)
1
35
0
Order By: Relevance
“…The use of GRL-0617 as a reference in the virtual screens facilitated the initial identification of 24 distinct scaffolds. Scaffold hopping has consistently been employed as an important tool in drug discovery and has yielded many active ligands thus far [ 91 , 92 , 93 ]. The availability of more than one scaffold is an advantageous starting point in any drug development process, given that attrition rates are high due to either lack of potency or poor pharmacokinetic profiles.…”
Section: Discussionmentioning
confidence: 99%
“…The use of GRL-0617 as a reference in the virtual screens facilitated the initial identification of 24 distinct scaffolds. Scaffold hopping has consistently been employed as an important tool in drug discovery and has yielded many active ligands thus far [ 91 , 92 , 93 ]. The availability of more than one scaffold is an advantageous starting point in any drug development process, given that attrition rates are high due to either lack of potency or poor pharmacokinetic profiles.…”
Section: Discussionmentioning
confidence: 99%
“…(−)‐Galantamine ( 1 ) was used to computationally screen a library of 3 383 942 commercially available compounds. The partial charge distribution and three‐dimensional shape of compounds were captured using the weighted holistic atom localization and entity shape (WHALES) descriptors, which were specifically developed for scaffold‐hopping from natural products to synthetic compounds. WHALES capture the shape and partial charge distributions of a three‐dimensional (3D) molecular conformer in terms of atom‐centered Mahalanobis distances, weighted by atomic partial charges.…”
Section: Figurementioning
confidence: 99%
“…(a) WHALES descriptors were calculated with Python v. 2.7, using in‐house software deposited on GitHub (https://github.com/grisoniFr/whales_descriptors.git, v.1). Gasteiger–Marsili partial charges were used as atomic description, as they resulted the best compromise between enrichment ability and scaffold‐hopping, and were computed using RDKit v. 2015.09.2 (default settings). Commercial library compounds and galantamine WHALES descriptors were normalized (Gaussian normalization) prior to virtual screening; commercial compounds were then sorted according to their Euclidean distance to galantamine (the lower, the better).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…From the resulting fine-tuned model, 1,000 SMILES strings were generated by applying fragment growing form from carboxy group and ranked according to the predicted biological target and similarity to know bioactivities. Predicted top-ranking compounds included reasonable activity on PPAR [17][18][19]. Miyao, Funatsu et al suggested a fundamental method for exhaustive structure generation by solving inverse QSAR equations in 2010 [20].…”
Section: Qsar: Quantitative Structure Activity Relationshipmentioning
confidence: 99%